Impact Of Training On The Performance Of School Teachers - Nova Syafrina (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2021)
The purpose of this study was to determine the effect of training on teacher performance at SMK Negeri Pertanian Terpadu, Riau Province. This research was conducted at Integrated Agriculture State Vocational School, Riau Province. This research was SMK Negeri Integrated Agriculture, Riau Province. sample in this study took the entire population, namely 89 people. The results based on hypothesis testing can be stated that training has a significant effect on performance. It is known that the contribution of training to performance is 37.7%, the rest is explained by variations in variables that do not exist in this study.